(In, Ga, Al)P–GaP laser diodes grown on high-index GaAs surfaces emitting in the green, yellow and bright red spectral range. (20th January 2017) - Ledentsov, N N; Shchukin, V A; Shernyakov, Yu M; Kulagina, M M; Payusov, A S; Gordeev, N Yu; Maximov, M V; Cherkashin, N A
Abstract: We report on low threshold current density (<400 A cm −2 ) injection lasing in (Al x Ga1– x )0.5 In0.5 P–GaAs-based diodes down to the green spectral range (<570 nm). The epitaxial structures are grown on high-index (611)A and (211)A GaAs substrates by metal–organic vapor phase epitaxy and contain tensile-strained GaP-enriched insertions aimed at reflection of the injected nonequilibrium electrons preventing their escape from the active region. Extended waveguide concept results in a vertical beam divergence with a full width at half maximum of 15° for (611)A substrates. The lasing at the wavelength of 569 nm is realized at 85 K. In an orange–red laser diode structure low threshold current density (190 A cm −2 ) in the orange spectral range (598 nm) is realized at 85 K. The latter devices demonstrated room temperature lasing at 628 nm at ∼2 kA cm −2 and a total power above 3 W. The red laser diodes grown on (211)A substrates demonstrated a far field characteristic for vertically multimode lasing indicating a lower optical confinement factor for the fundamental mode as compared to the devices grown on (611)A. However, as expected from previous research, the temperature stability of the threshold current and the wavelength stability were significantly higher for (211)A-grown structures.